Assessing Use Errors Related to the Interface Design of Electrosurgical Units. (4th January 2018) - Estock, Jamie L.; Li, Airan; Casey, Maureen C.; Taylor, Matthew A.; Boudreaux‐Kelly, Monique Y.; Choma, Martin D.; Jacobs, Katrina; Eibling, David E.
Abstract: Medical device use errors, such as instrument connection errors made with electrosurgical units (ESUs), can lead to adverse events. Current device acquisition processes at health care facilities do not typically include a proactive evaluation of use‐error risk before device purchase. We conducted an evaluation to identify ESU user interface design features that can help prevent or mitigate instrument connection errors during clinical care. Thirty‐six current ESU users participated in the evaluation. We used a randomized crossover design in which each participant used two ESU models in a simulated OR scenario. We compared participants' instrument connection accuracy, efficiency, and subjective feedback regarding the user interface design across the two ESU models. Overall, we found that the ESU model that incorporated more user interface design principles resulted in better performance and increased acceptance from users. Based on the results, we designed a decision‐support tool to assess the risk of instrument connection errors before ESU purchase.